Plan promoción y prevención para disminuir la incidencia de dengue hemorrágico en edad pediátrica en el Hospital Teófilo Dávila el primer semestre del 2010. - Mendieta Carpio, María F. (2011)
The HTD – Machala. Department of pediatrics study was conducted case series, descriptive dengue positive cases in children younger than 12 years in the period January 2010 to June 2010, in order to determine the clinical and epidemiological disease classification according to who, to identify associated pathologies, to determine antibody titers and serotypes and presentation describe the trend over time.